Prostaglandin F2α and its interference on pregnancy rates in heifers - Maziero Guaitolini, Rosiara Rosaria Dias; Elias, Alecsandro Silva de Lima; Guaitolini, Carlos Renato Freitas; Araujo, Alyson Liberali; Crespilho, Andre Maciel (Archives of Veterinary Science, 2024)
The present study aimed to evaluate the pregnancy rate of Nellore and Crossbred heifers submitted the induction of puberty with prostaglandin PGF2α. Control group (n=80), heifers were submitted to a fixed-time artificial insemination protocol (FTAI), without pre-exposure to any hormone, induction group (n=80), Nellore (n=80) and Crossbred (n=80) females were submitted to two applications of prostaglandin PGF2α prior to the FTAI protocol, 24 days before the beginning of the protocol (D-24) and twelve days before the start of the protocol (D-12). All heifers were aged between 12 and 14 months, with an average weight of 311 kg and body condition score 3. FTAI protocol, both groups were performed: on day 0 (D0), there was the application of estradiol benzoate and insertion of the intravaginal implant with progesterone. On day eight (D8), implant was removed and equine chorionic gonadotropin, prostaglandin, and estradiol cypionate were applied. On day 10, artificial insemination was performed. Thirty days after FTAI, pregnancy was diagnosed by transrectal ultrasound. The animals were individually weighed to verify the interaction between weight and pregnancy rates. For statistical analysis SAS 9.3 software was used. The results were considered different with a significance level of 5%. For animals in the Induction group, pregnancy rates at 30 days after FTAI (P˃0.05) were 57.5% (46/80) for Nellore heifers and 52.5% (42/80) for Crossbred heifers. Control group, heifers had a pregnancy rate of 60% (48/80) (P˃0.05). No interaction was observed between heifer weight and conception rate in the FTAI, regardless of the induction treatment (P=0.1897). Furthermore, there was no difference in the pregnancy rate between Nellore (P=0.5389) and Crossbred females (P=0.4425), which were submitted to application of PGF2α before starting the FTAI protocol. Thus, it could be concluded that there was no difference in the pregnancy rate with the induction of puberty using the PGF2α.